The Tradition of Reading Surat Al Kahfi at The Al Qur'an Islamic Boarding School Gumawang Wiradesa Pekalongan: Tradisi Pembacaan Surat Al Kahfi di Pondok Boarding School Al Qur’an Gumawang Wiradesa Pekalongan - Salsabila, Zhafarina; Muhammad Faqih Ahkam (Aqwal: Journal of Qur'an and Hadis Studies, 2024)
Background and Objectives: The integration of Quranic practices into daily life, and their influence on society and individuals. One of them is the recitation of Surat al-Kahf at the Quranic Boarding School, Gumawang, Wiradesa, Pekalongan. The tradition of reciting Surat al-Kahf at Pondok Pesantren Al-Qur'an Gumawang every Friday is not only a religious obligation, but also an important part of the spiritual and moral development of the students. The purpose of this article is to understand the phenomenon of reciting Surah al-Kahf at the Qur'anic Boarding School, Gumawang, Wiradesa. Method: The research method that will be conducted is the Living Quran method which interprets the Qur'an as a valuable entity in life. The research data will be collected through interviews and literature study, which will then be analysed using descriptive analytical method. The author will describe the data findings systematically and factually based on the data collected. Main findings: This study found that the tradition of reciting Surah Al-Kahf at the Gumawang Qur'anic Boarding School is not only a routine worship practice, but also part of the Living Qur'an approach which emphasises understanding and internalising Qur'anic values in daily life. The main contribution of this research is to provide insight into a model of Qur'anic education that is not only oriented towards intellectual aspects, but also includes character building and the practice of Islamic values in social life. Conclusion: the study of the recitation of Surah Al-Kahf in Pondok Boarding school Al-Qur'an Gumawang, Wiradesa, Pekalongan which has become a tradition developed and embedded through reading, reflection and discussion. This tradition becomes a tool for developing a deep understanding of the values contained.